PENGARUH KOMPENSASI LANGSUNG, KOMPENSASI TIDAK LANGSUNG SERTA KESEHATAN DAN KESELAMATAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN (STUDI PADA PT. PUPUK SRIWIJAYA, PALEMBANG) - Puspita Sari, Septia Wahyuni; Yuniawan, Ahyar (Faculty of Economics and Business Diponegoro University, 2017)
Problems that occur in the PT. Pupuk Sriwijaya Palembang is a decrease in employee productivity. It is shown from a decrease in the production target of PT. Pupuk Sriwijaya Palembang where production achievement never reached the target set by the company. Decrease in employee's productivity is thought to be caused due to several factors namely direct compensation, indirect compensation, occupational safety and health. This study aimed to analyze the influence of direct compensation, indirect compensation, occupational safety and health on employee productivity PT. Pupuk Sriwijaya Palembang.The population used in this study employees of PT. Pupuk Sriwijaya Palembang. The sampling technique used was purposive sampling. Criteria samples taken is the production employees of PT. Pupuk Sriwijaya Palembang who have worked at least three years amounted to 118 employees. Methods of data collection in this study using questionnaires and interviews. Methods of data analysis using multiple linear regression analysis.Based on this research, direct compensation, indirect compensation, occupational safety and health a positive effect on employee productivity PT. Pupuk Sriwijaya Palembang. Productivity of labor was explained by direct compensation, indirect compensation, and occupational health and safety amounted to 74.4%.